Bioorthogonal Fluorescent Labeling of Functional G‐Protein‐Coupled Receptors. Issue 12 (18th July 2014) - Tian, He; Naganathan, Saranga; Kazmi, Manija A.; Schwartz, Thue W.; Sakmar, Thomas P.; Huber, Thomas
Abstract Novel methods are required for site‐specific, quantitative fluorescent labeling of G‐protein‐coupled receptors (GPCRs) and other difficult‐to‐express membrane proteins. Ideally, fluorescent probes should perturb the native structure and function as little as possible. We evaluated bioorthogonal reactions to label genetically encoded p‐acetyl‐L‐phenylalanine (AcF) or p‐azido‐L‐phenylalanine (azF) residues in receptors heterologously expressed in mammalian cells. We found that keto‐selective reagents were not truly bioorthogonal, possibly owing to post‐translational protein oxidation reactions. In contrast, the strain‐promoted [3+2] azide–alkyne cycloaddition (SpAAC) with dibenzocyclooctyne (DIBO) reagents yielded stoichiometric conjugates with azF‐rhodopsin while undergoing negligible background reactions. As one application of this technique, we used Alexa488–rhodopsin to measure the kinetics of ligand uptake and release in membrane‐mimetic bicelles using a novel fluorescence‐quenching assay.